(untitled) (Ameghiniana, 2013)
An almost complete mandible of Patene simpsoni (Marsuplalia, Borhyaenidae, Hathlyacyninae) from Lumbrera Fm. (Casamayoran Age, early Eocene) of Salta Province, Argentina, is described. By means of a sedimentary analysis of this formation, there can be distinguished five facies: St, Sp, Sr, Sh and FI-Fm. From a palaeoenvironmental point of view, this formation appears related to a meander system, with the Iluctuant variations that characterize ephemeral interlaced rivers. The sedimentary sequence reflects alternative conditions, probably corresponding to humid and dry epochs. The material examined represents the first record of a mandíble of Patene simpsoni, and extends its known range from Itaboraian Age (middle Paleocene) to Casamayoran Age (Eearly Eocene). P. simpsoni shares some morphological features with several Didelphoídea from the South American Paleogene, specially with those from tbe Paleocene of Itaboraí, Brasil (e.g., p3 notably enlarged in relation to p2.). Nevertheless, it already shows those features that define a more intense carnassialization, typical of the Borhyaenídae (e.g., reduced metaconid and smaller than paraconíd ). This assocíation of specialized fea tu res is interpreted as prernonitory to the more advanced Borhyaenoidea, and as distinguishing it from the known Didelphoídea. Climatic-environmental differences between the North of Argentina and Patagonia during early Eocene could explain the morphological difference Found among the two known species of Patene, P. simpsoni and P. coluapiensis. In turn, the presence of P. simpsoni up to early Eocene, at least, in the present intertropical regions seems to indicate the ertdurance there of the envíronmental conditions that characterized the Paleocene high latitudes.